PARADIGMA MANAJEMEN DALAM AL QURAN - Muhammad Ridwan Alwahab; Dewi Sartika; Sasta Nabila Putri; Eka Apri Yanti (ICONS: Islamic Economics Journal, 2025)
This article exsplores the management paradigem in the qur’an,ekxploring the ethical,leader ship and organizational principles containet in islam’s sacred tex.the qur’an is not only a spiritual guide,but also provides a strong at hical foundation for sustainable and moral management.In this article we will explore how the palues and teachings in the quran cangguide leaders and managers in managing their organizatins well.manjemen is the most important element in the Islamic legal thought segmen because it is directly related to the regulatons off social institutions.Managemen at build on the principles of quality,justice and fullfilmen of rig hts and obligations. The principle of equality in Islam must be appreciated absolutely in order to create an Islamic system that combines freedom and responsibility. Normatively, the above principles have been mentioned in sacred teaching texts, both the Qur'an and the Sunnah. In practice, these principles need to be actualized according to the context of change and development in society. As social creatures, humans continue to interact with their surrounding environment, therefore, a set of rules (fiqh) is needed that can accommodate these social interaction issues in accordance with the principles of equality and benefit. For this purpose, the theories or norms in the Qur'an and al-Hadith need to be implemented in real life, contextually according to the reality of developments that are occurring in almost all walks of life. nationality and patriotic. In this Islamic management segment, it is very important that the principles the principles of equality, justice, openness, intelligence, innovation and creativity with the concept